God's gold : a quest for the lost temple treasures of Jerusalem - Kingsley, Sean. (New York, NY : HarperCollins, 2007)
Traces an archaeologist's search for the ancient Jerusalem Temple treasure, a fifty-ton cache of gold, silver, and jeweled relics for which the author researched nearly two millennia of history and embarked on a series of labyrinthine quests.
River of gold -- Awakenings -- Ghosts of Israel past -- Exodus and exile -- Herod's treasure chest -- Dark secrets in the Vatican -- Temple prophecies -- Volcano of hate -- Keeping the faith? -- Benjamin of Tudela -- The philosopher's folly -- Dead sea treasures -- Castles in the Air -- Divine light: the Menorah -- Hunting graven images -- The tree of life -- Bread of Heaven -- Trumpeting messages -- City of unbrotherly love -- Turning the screw -- Death of a temple -- Flavian spin -- Walking with God -- A word from the sponsors -- Aliens in Rome -- Of circuses and artichokes -- The triumphal way -- A day at the circus maximus -- A temple for peace -- Jewish gold, barbarian loot -- Heresy and holocaust -- Keeping the faith -- In a Vandal palace -- Treasures recycled -- Hunting hippodromes -- Imperial war games -- Sanctuary of the Christians -- Desert city of saints -- City of gold, world of man.
Includes bibliographical references (p. 301-308) and index.
English.
Keywords: Treasure troves -- Jerusalem -- History; Temple of Jerusalem (Jerusalem); Palestine -- Antiquities; Temple of Jerusalem (Jerusalem) -- History; Buried treasure -- Religious aspects -- Judaism; Cultural property -- Jerusalem